Spectrophotometric Determination of Erbium(III) with Murexide in Synthetic Samples - Turkoglu, Orhan; Soylak, Mustafa; Colak, Hakan (Asian Journal of Chemistry, 2010)
A sensitive, facile and simple method for the determination of trace amounts of erbium by spectrophotometry is described based on the formation of the erbium-murexide complex. Beer's law is obeyed from 0.1-5.0 mg/L of erbium at 463 nm as Er-murexide complex. Optimal conditions such as reagent amounts, pH for the erbium determination were reported. The effects of the foreign ions were also investigated. The proposed method was successfully applied to the determination of erbium contents in synthetic samples.